Occupational mobility in Europe: Extent, determinants and consequences - Ronald Bachmann; Peggy Bechara; Christina Vonnahme (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
We examine occupational mobility and its link to wage mobility across a large number of EU countries using worker-level micro data. In doing so, we document the extent, the individual-level determinants and the consequences of occupational mobility in terms of wage outcomes and structural change across the EU. In addition, we identify potential explanations for the observed cross-country variation. Our results show that on average, 3% of European workers change their occupation per year, and that the extent of occupational mobility differs strongly by country. Individual characteristics play an important role for person-specific occupational mobility, but have little explanatory power for differences between countries. Occupational mobility is strongly associated with earnings mobility, and occupation movers are more likely than job movers to experience a downward rather than an upward earnings transition; by contrast, changing occupation voluntarily is more often followed by an upward wage transition. As opposed to composition effects, labour-market institutions, especially employment protection legislation, seem to play an important role for explaining crosscountry differences in occupational mobility. – – In dieser Studie werden berufliche Mobilität und deren Zusammenhang zu Lohnmobilität für eine große Anzahl von EU-Ländern mit Hilfe von Mikrodaten auf Ebene der Beschäftigten untersucht. Dadurch können sowohl das Ausmaß und die auf individueller Ebene wirkenden Determinanten als auch die Effekte von beruflicher Mobilität auf Löhne und strukturelle Veränderungen in der EU aufgezeigt werden. Zusätzlich werden mögliche Erklärungsfaktoren für die zu beobachtenden Länderunterschiede identifiziert. Unsere Ergebnisse zeigen, dass im europäischen Durchschnitt pro Jahr 3% der Beschäftigten ihren Beruf wechseln, wobei das Ausmaß der beruflichen Mobilität stark zwischen den einzelnen Ländern variiert. Individuelle Charakteristika spielen zwar eine große Rolle für die berufliche Mobilität einzelner Beschäftigter, tragen aber wenig zur Erklärung der Unterschiede zwischen den Ländern bei. Berufliche Mobilität ist eng mit Lohnmobilität verknüpft. Berufswechsler haben eine höhere Wahrscheinlichkeit als Stellenwechsler, eine Abwärts- anstelle einer Aufwärtslohntransition zu erfahren. Freiwillige Berufswechsler hingegen vollziehen öfter Aufwärtstransitionen. Im Gegensatz zu Kompositionseffekten spielen Arbeitsmarktinstitutionen, insbesondere der Kündigungsschutz, eine wichtige Rolle zur Erklärung der länderspezifischen Unterschiede bezüglich beruflicher Mobilität.
Keywords: J62; J63; P52; 330; occupational mobility; job mobility; wage mobility; European labour markets; EU-SILC; cross-country study